Pengaruh Store Atmosphere, Kualitas Pelayanan, Dan Kualitas Produk Terhadap Keputusan Pembelian (Studi pada mahasiswa konsumen produk dazzle di universitas sarjanawiyata tamansiswa yogyakarta) - Prasetyo, Arief; Fadhilah, Muinah; Cahyani, Putri Dwi (Universitas Muhammadiyah Metro, 2021)
This study uses a store atmosphere, service quality and product quality influence purchasing decisions. The research objective was to determine the effect of store atmosphere, service quality, and product quality to influence Dazzle consumer purchasing decisions at Jalan Gejayan. The population in this study were active students of the Universitas Sarjanawiyata Tamansiswa Yogyakarta who were Dazzle consumers, with a total sample of 100 students. This study uses multiple linear regression analysis techniques in data processing where this technique is used to estimate the value of the dependent variable by using more than one independent variable. The results of the analysis found that there were; (1) Store atmosphere has a positive and significant effect on purchasing decisions, (2) Service quality has a positive and significant effect on purchasing decisions, (3) Product quality has a positive and significant effect on purchasing decisions, (4) Store atmosphere, service quality, and quality The product simultaneously has a positive and significant effect on purchasing decisions with the F value obtained (84,670). The most dominant variable in this study is product quality with a value of 5.841 and a significant value of 0.000.